A novel role for granzymes in anti-tumor immunity - Hoves, Sabine (Landes Bioscience, 2012)
The cytotoxic properties of granzymes are well established, though recent publications suggest additional roles for granzymes in immunity. We demonstrated that granzymes can act as regulators of cross-presentation by dendritic cells by inducing critical “eat-me” signals on the dying tumor cell, resulting in efficient phagocytosis of cell-associated tumor antigen.